Strategi Pengembangan Pasar Produk Smart Business Card PT Teknologi Mudah Terhubung (TAPPP) ke Singapura Menggunakan Ansoff Matrix dan SWOT - Iqlima, Lubna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to formulate a market development strategy for PT Teknologi Mudah Terhubung’s (Tappp) Smart Business Card in Singapore using SWOT analysis and the Ansoff Matrix. A mixed-method approach was applied, combining qualitative interviews with Tappp’s management and quantitative surveys with internal stakeholders. Secondary data were sourced from company reports, official publications, and relevant literature. SWOT analysis identified strengths such as NFC/QR-based product innovation, customization flexibility, and a freemium business model, alongside weaknesses including limited production capacity, lack of international marketing expertise, and low brand awareness in Singapore. Opportunities stem from Singapore’s growing digital ecosystem, pro-innovation regulations, and networking trends, while threats include competition from local providers, import regulations, and cultural differences. The Ansoff Matrix index highlighted product development (99%) and market development (91%) as key priorities. Recommended strategies include local partnerships, enhanced digital marketing, product feature differentiation, and targeting niche markets. These findings provide strategic guidance for Tappp and other local tech startups expanding internationally.